'Once For All': The Tense of the Atonement - Le Poidevin, Robin (European Journal for Philosophy of Religion, 2016)
Does a proper understanding of the Atonement – the restoration of mankind’s relationship with God as a result of Christ’s sacrifice – require a particular conception of time? It has been suggested that it does, and that the relevant conception is a ‘tensed’ or ‘dynamic’ one, in which distinctions between past, present and future reflect the objective passage of time. This paper examines two arguments that might be given for that contention, and finds that both may be answered by appeal to the asymmetry of causation. The Atonement leaves us free to think of all times as equally real, as traditionally they are for God.